Writing "SMMART" Objectives - Lisa A. Guion; Eboni Baugh; Jade Marcus (EDIS, 2006)
Setting SMMART objectives allows Extension educators to accomplish a number of tasks. It allows for efficient evaluation of programs by determining target audience, realistic expected outcomes, timeframe, measurement criteria, etc. These objectives serve as a foundation for determining program success and effectiveness. Creating SMMART objectives is a vital step in program planning for Extension professionals. This document is FCS6016, one of a series of the Family,Youth and Community Sciences Department, UF/IFAS Extension. Original publication date May 23, 2006.